2020
DOI: 10.1186/s12891-020-03741-0
|View full text |Cite
|
Sign up to set email alerts
|

A patients’ view of OA: the Global Osteoarthritis Patient Perception Survey (GOAPPS), a pilot study

Abstract: Background Globally, osteoarthritis (OA) is the third condition associated with disability. There is still poor treatment in OA but science holds the key to finding better treatments and a cure. It is essential to learn what’s important to patients from them to implement the most effective OA management. The OA Patients Task Force, conducted the Global OA Patient Perception Survey (GOAPPS)-the first global survey made by patients to analize the quality of life (QoL) & patient perceptions of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 37 publications
0
15
0
2
Order By: Relevance
“… 40 Moreover, evidence showed that individuals with OA are seeking non‐pharmacological and non‐surgical treatments for their conditions, and they want more information about these treatments, which highlights the likelihood that they might be open to undergoing exercise and physiotherapy interventions if educated on their benefits. 41 , 42 This was also retrieved in our interviews in which patients understood the importance of being active and saw exercise as a concrete support to their care, something that one can see while doing it, in contrast to medications and supplements that do not immediately show tangible effects.…”
Section: Discussionmentioning
confidence: 92%
“… 40 Moreover, evidence showed that individuals with OA are seeking non‐pharmacological and non‐surgical treatments for their conditions, and they want more information about these treatments, which highlights the likelihood that they might be open to undergoing exercise and physiotherapy interventions if educated on their benefits. 41 , 42 This was also retrieved in our interviews in which patients understood the importance of being active and saw exercise as a concrete support to their care, something that one can see while doing it, in contrast to medications and supplements that do not immediately show tangible effects.…”
Section: Discussionmentioning
confidence: 92%
“…However, a study by Vitaloni et al concluded that patients are seeking non-pharmacological and non-surgical treatments for their conditions which highlights the possibility that patients might be open to undergo exercise and physiotherapy interventions if educated on their benefits and importance. 47 …”
Section: Discussionmentioning
confidence: 99%
“…With no cure, and no proven interventions able to stop its' progression (OARSI 2016), it is a major cause of disability worldwide with increasing prevalence. The consequences of OA impact signi cantly on individuals and wider society (Versus Arthritis 2021), highlighting the urgent need for increased investment into large scale scienti c and clinical research (Vitaloni et al 2020).…”
Section: Research Objectivementioning
confidence: 99%